2023
DOI: 10.3390/act12070266
|View full text |Cite
|
Sign up to set email alerts
|

Design, Topology Optimization, and Additive Manufacturing of a Pneumatically Actuated Lightweight Robot

Abstract: Soft robotics research has rapidly incorporated Additive Manufacturing (AM) into its standard prototyping repertoire. While numerous publications have highlighted the suitability of AM for producing soft pneumatic actuators, fluidic components, and lightweight structures, their integration into an industry-like robotic arm has not yet been shown. Against this background, a pneumatically actuated robot was developed that incorporates additively manufactured soft structures into rigid articulated hinges that gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…From Section 4, it is found that the proposed method yields good results by minimizing the maximum compliance when solving TO problems under multiple-loading conditions compared to the TEWS method. On the other hand, past research has considered that the proper optimization solution can be obtained for multiple objectives with different degrees of importance by changing the weight factors (WS methods, [29,[34][35][36][37][38][39][40][41][42]). In this section, the features of the proposed method and its advantages are discussed by comparing the TO results between this method and the WS methods (including the TEWS method in Stage 1 of the proposed framework).…”
Section: Comparison Of the Proposed Methods With The Weighted Sum Met...mentioning
confidence: 99%
See 2 more Smart Citations
“…From Section 4, it is found that the proposed method yields good results by minimizing the maximum compliance when solving TO problems under multiple-loading conditions compared to the TEWS method. On the other hand, past research has considered that the proper optimization solution can be obtained for multiple objectives with different degrees of importance by changing the weight factors (WS methods, [29,[34][35][36][37][38][39][40][41][42]). In this section, the features of the proposed method and its advantages are discussed by comparing the TO results between this method and the WS methods (including the TEWS method in Stage 1 of the proposed framework).…”
Section: Comparison Of the Proposed Methods With The Weighted Sum Met...mentioning
confidence: 99%
“…Thus, it is easier to obtain one or more optimal solutions by solving the transformed problem(s) [35]. Among these methods, the weighted sum (WS) method [29,[34][35][36][37][38][39][40][41][42] for multi-objective optimization is widely utilized, which involves assigning weights to each objective and determining a compromised solution. This method not only allows for the generation of multiple solution points by adjusting the weights accordingly but also enables obtaining a single solution point reflecting preferences linked to a specific set of weights.…”
Section: Topology Optimization Considering Multiple-loading Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a second extremely important step, FEA are used to perform an optimization of the shape and dimensions of each component, a set of characteristics often defined as "topology" [8]. It is possible to model the component geometry, reinforcing the areas where a high strength is needed and lightening other ones where reinforcing material is not necessary [9,10]. Two examples are reported below, for describing more clearly how this approach was used.…”
Section: "Design By Analysis"mentioning
confidence: 99%
“…A quest for particularly lightweight, compact, and affordable systems with compliant and back-drivable behavior [ 1 ] has given rise to a variety of actuation concepts. Pneumatic actuators have attracted interest because of their simple design, low weight, and low cost, and functional prototypes of pneumatically actuated robots with articulated joints have already been described [ 2 , 3 , 4 ]. In soft robotics where different compliant actuation methods, such as electrohydrodynamic devices [ 5 ], are researched, the easily manufacturable pneumatic actuators are still the most common [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%